Effect of Working Capital Turnover and Turnover Receivables on Company Profitability Food and Beverage Sector Manufacturing Registered on the Indonesia Stock Exchange - Mediaty, Mediaty; Rachmatullah, Muhammad; Habbe, Abdul Hamid (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
This study aims to accomplish three primary objectives: firstly, to assess the impact of partial working capital turnover on profitability; secondly, to examine the influence of partial loan turnover on profitability; and thirdly, to investigate the combined effect of working capital turnover and loan turnover on profitability. The variables under scrutiny include profitability, denoted as the dependent variable (Y), measured through return on assets, and independent variables (X) comprising working capital turnover and receivables turnover. The research is conducted on the population of all manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange, with a sample of 17 companies selected over a 3-year period using a saturated sampling technique. Data collection involves the utilization of documentation techniques. Analysis entails classic assumption testing, multiple linear regression analysis, coefficient of determination testing, t-tests, and F-tests, facilitated by SPSS software. The findings indicate that, overall, working capital turnover and receivables turnover do not collectively exert a significant impact on profitability. Additionally, the study reveals that partial working capital turnover, when examined in isolation, and partial receivables turnover do not individually exhibit a significant effect on profitability.